Politics, religion and freedom in Augusto Del Noce and Erik Peterson (Cultura Económica, 2021)
This work explores coincidences between two authors who have rarely been connected: Erik Peterson and Augusto Del Noce. Departing from theology and philosophy respectively, they both discover in the sacralization of power the degeneration of politics, far from how it should be conceived in a Christian way. They reach out to Augustine to apply his distinction between the two cities, in order to prevent an immanentization of the eschatological and a subjugation of personal freedom. The reflection on martyrdom and testimony in the democratic game offer a suggestive cooperation, respectful of the search and personal attachment to the truth, not conceiving politics as an intrinsic conflict.
Keywords: POLITICAL PHILOSOPHY; AUGUSTO DEL NOCE; MODERNITY; TOTALITARIANISM